2010
DOI: 10.1017/s1047951110001447
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of atrial tachyarrhythmias late after surgical repair of tetralogy of Fallot

Abstract: Patients with surgically repaired tetralogy of Fallot and atrial tachyarrhythmias typically have multiple arrhythmic circuits/foci arising from a scarred right atrium. Catheter ablation reduces arrhythmia frequency and improves symptoms. However, hybrid management is often required, comprising drugs, pacing, and further surgery tailored to the individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Mechanisms and outcomes have only been described in a small number of previous studies. [12][13][14] De Groot et al 12 described a comparable large proportion of cavo-tricuspid isthmus-dependent tachycardia with scar-dependent intra-atrial re-entrant tachycardia, and similarly reported acute success rates of 98% with sinus rhythm maintained in~85% at long-term follow-up. They also observed a similar incidence of atrial fibrillation during follow-up but did not describe left atrial ablation in their patients.…”
Section: Discussionmentioning
confidence: 98%
“…Mechanisms and outcomes have only been described in a small number of previous studies. [12][13][14] De Groot et al 12 described a comparable large proportion of cavo-tricuspid isthmus-dependent tachycardia with scar-dependent intra-atrial re-entrant tachycardia, and similarly reported acute success rates of 98% with sinus rhythm maintained in~85% at long-term follow-up. They also observed a similar incidence of atrial fibrillation during follow-up but did not describe left atrial ablation in their patients.…”
Section: Discussionmentioning
confidence: 98%
“…26,27 Given the complex atrial substrate in the patient with TOF, a hybrid approach consisting of medications, pacing, and further surgery tailored to the individual may be required. 17…”
Section: Ablationmentioning
confidence: 99%
“…6,22–24 Multiple AA mechanisms may coexist in the same patient and typically involve a combination of the cavotricuspid isthmus, scar-based macroreentrant tachycardia, or a focal atrial tachycardia, thereby requiring complex ablations. 11,17,18,25…”
Section: Atrial Tachyarrhythmias and Sinus Node Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations